2005
DOI: 10.1081/css-200056896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Composted Olive Cake on Soil Physical Properties

Abstract: Large areas in Jordan are planted with olive trees, resulting in the production of large amounts of olive cake (OC) and annually imposing a disposal and pollution burden. This research examined the use of OC compost as a soil amendment and its effect on soil physical properties such as soil water retention and infiltration in terms of depth of penetration and accumulated intake on two soil types: clay (S1) and silt loam (S2). Composting was intended to reduce the harmful effects of untreated OC. Olive cake was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
(10 reference statements)
1
4
0
Order By: Relevance
“…The water accumulate intake (mL) is shown in Table 3 for clay soil and Table 4 for sandy clay soil as affected by addition of olive cake. The data shows that accumulate intake increased as olive pomace application rate increased, this in agreement with [3] , [4] , [6] , [7] .…”
Section: Datasupporting
confidence: 80%
“…The water accumulate intake (mL) is shown in Table 3 for clay soil and Table 4 for sandy clay soil as affected by addition of olive cake. The data shows that accumulate intake increased as olive pomace application rate increased, this in agreement with [3] , [4] , [6] , [7] .…”
Section: Datasupporting
confidence: 80%
“…However, the comparison among data from compost treatments and those of the infested and noninfested controls may suggest that the growth effect of the tested materials may be concurrently due to an increased plant nutrition, as exerted mainly by C 1 and C 3 , as well as to the nematode suppression, prevailing in the soil amended with C 4 . Composts from many raw materials, among which manures and FOP, were reported for a general improvement of physical soil properties and availability of nutrients (Sasanelli et al, 2002;Al-Widyan et al, 2005), though in our experiment N t content was consistently enriched only at the highest rates of the five materials and OM content was improved mainly by FOP composts. Finally, the soil pH was not affected by compost amendments and, therefore, could not be related to their nematicidal effect.…”
Section: Conclusion and Discussionmentioning
confidence: 36%
“…It is expected that using compost will enhance plant growth because of its physical and chemical properties (Al-Widyan et al, 2005;Paredes et al, 2005). Indeed, OM provided by compost Fig.…”
Section: Potato Cultivationmentioning
confidence: 99%
“…Research on this topic has shown that composting olive cake under well-defined conditions allows the production of composts having a fertilizing capacity comparable to that of ''conventional manure" (Hachicha et al, 2003;Al-Widyan et al, 2005). By composting OMW, researchers have obtained composts with a high level of humic compounds (Alburquerque et al, 2006;Baeta-Hall et al, 2005;Hachicha et al, 2006;Paredes et al, 2005;Tomati et al, 1996).…”
Section: Introductionmentioning
confidence: 97%